AUGMENTED REALITY IN CUSTOMER EXPERIENCE AS A SALES DRIVER IN THE RETAIL SECTOR: A SYSTEMATIC LITERATURE REVIEW - NEGRILLO, JEAN PAUL; VILA, NICOLE (LACCEI, 2025)
The article explored how augmented reality (AR) transformed the customer experience in the retail sector and its contribution to increased sales. According to recent studies, it was highlighted that AR offered consumers the possibility to virtually interact with products before making a purchase, which not only increased their confidence in decisions but also streamlined the purchasing process. This technology resulted in an outstanding improvement in consumer satisfaction by providing an immersive, personalized and engaging shopping experience. In addition, AR reinforces customer loyalty by making interaction with brands more dynamic, which increases the likelihood of future purchases. By reducing uncertainty about products, it also reduces the number of returns, benefiting both consumers and companies. However, its adoption presents certain challenges, such as technological costs and integration into existing systems. Despite these obstacles, AR is emerging as a key tool for companies to stand out in a highly competitive market. Ultimately, AR is changing the way stores connect with their customers, and its potential to redefine commerce is increasingly evident, becoming an essential strategy for the future of retail.